Development and analysis of drone impacting into a human - Wong, Khia Chen (Nanyang Technological University, 2022)
This study is to develop and analyse the crash seriousness between UAVs and humans. A generalised fixed-wing drone was created using SolidWorks. The impact forces and the crash seriousness were computed by utilising the explicit dynamic simulation on ABAQUS. In this study, 3 materials, Aluminium, Carbon Fibre, and Expanded Polypropylene (EPP), were assigned to the fixed Maximum Take-Off Mass (MTOM) values of 0.25 kg, 0.5 kg, 1.5 kg, 3.5 kg according to EASA’s ‘Open Category’. The impact velocity was fixed to 30 m/s. The Abbreviated Injury Severity (AIS) were coded according to the impact force by utilising the Impact Force Criterion. The results show that as the MTOM increase, the impact force will increase. The results show that a carbon fibre or aluminium generalised fixed-wing drone can cause severe injuries even if the drone is under the ‘Harmless’. The results also show that a low density and low rigidity material like EPP can cause serious injury when the MTOM is above 3.5 kg. Further studies are required to study more commonly used materials and physical experiment is required to validate the study done by this FYP Report.